Bentuk Sapaan Kekerabatan Bahasa Sula dalam Perspektif Gender - Nurhayati Fokkaya (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
In gender perspective of Sula language, there is a different form of addressing male and female in nucleus family. This can be seen in the use of second single pronoun mon “you” and gu “you”. This kind of addressing covers the usual dimension or (unequal) and is used by anyone. More dominantly, women use polite addressing (equivalent) when greeting men, as in the word kim “you” referred to singular pronoun and gi “you” referred to plural pronoun. in Sula kinship, the word "kim" and "gi" are considered to be more prestigious in social status and more polite. This study aims to identify the forms of kinship address in nucleus family from the perspective of gender. This is a qualitative research and the technique of collecting data involves the activities of observing, listening, noting, and recording.